ANALISIS PENINGKATAN AKUNTABILITAS PENGELOLAAN KEUANGAN DESA MENGGUNAKAN APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DI DESA MARGA MULYA KECAMATAN RANTAU RASAU - Habriyanto Habriyanto; Muthmainnah Muthmainnah; Miftakhul Huda (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The development of the public sector in Indonesia is currently strengthening the demand for the implementation of public accountability and transparency in government and politics, especially in the financial sector, which is a consequence that needs to be resolved when entering the autonomy paradigm. Accountable village financial management is management that must be accountable from planning, budgeting, management, and financial reporting activities. Achieving accountability is the main goal of the sector Public. The Financial and Development Supervisory Agency (BPKP), which has the task of supervising the village financial accountability system, then develops an application for village financial management, namely the village financial system or commonly known as Siskeudes.This research uses a qualitative descriptive method. This study aims to find out how to increase the accountability of village financial management in Marga Mulya village by using the village financial system application (siskeudes) and the role of the community in the realization of village accountability. The research can conclude that the quality of accountability after using the Siskeudes application is very good and the community has played a sufficient role in the realization of village financial accountability by taking part in musdes and being critical of village fund management, However, there are still several problematic aspects of village financial management that have the potential to make room for financial problems.The use of the Village Financial System (Siskeudes) application in Marga Mulya Village, Rantau Rasau District is in accordance with the provisions. limited human resources to lack of assistance in the implementation of the Siskeudes application.